EKONOMI SYARIAH DI BALIK TEMBOK PESANTREN: STUDI TENTANG MODEL KEMANDIRIAN FINANSIAL LEMBAGA PENDIDIKAN ISLAM TRADISIONAL - Khuzaini, Nanang; Hilmy, Masdar; Nasrulloh, M. Farid; Kartiko, Ari (Prodi Pendidikan Agama Islam, 2026)
This research investigates the complexity of the financial independence model of Islamic boarding schools (pesantren) in Indonesia through an integrative lens of social science, culture, and Islamic economics. Pesantren function not only as the epicenter of traditional Islamic religious education, but also as independent socio-economic-cultural entities, forming a unique economic ecosystem that is deeply embedded in religious values, social norms, and local wisdom. Employing a qualitative approach with an in-depth multi-location case study strategy, this research reveals that the financial independence of pesantren is built and sustained through the mutualistic symbiosis of three main pillars.